THE ANALYSIS OF FACTORS AFFECTING EMPLOYEES WORK MOTIVATION AT KANTOR KECAMATAN PONTIANAK UTARA - B12111017, Aristia Widyasari (Jurnal Manajemen Update, 2015)
The purpose of this study is to examine the factors that affecting employees’ work motivation. There were two factors that chosen for this research which are job satisfaction and compensation. The research is done by descriptive analysis and multiple linear regression as it was counted with using SPSS 20. The primary data was gathered using questionnaire based on 70 employees of Kantor Kecamatan Pontianak Utara. The results of the study revealed that job satisfaction and compensation simultaneously have positive impact on employees’ work motivation and partially shows that  job satisfaction has no significant affect on employees’ work motivation while  compensation significantly affects employees’ work motivation at Kantor Kecamatan Pontianak Utara. Keywords : Job satisfaction,compensation,motivation.